Generalized Implementation of Switching-Loss-Minimized Space-Vector Modulation for Three-Level Converters - Pai, Ajay Poonjal; Siddique, Hafiz Abu Bakar; De Doncker, Rik W. (Technische Universität Dortmund, 2015)
With increasing integration of the intermittent and volatile renewable energy resources into the existing ac grid infrastructure, the grid stability is decreasing. Large battery storage systems are proposed to act as short-time buffer to cope with transient instabilities. A promising converter to interface such low-voltage high-power battery banks is the T-type Neutral- Point-Clamped Converter (TNPC). A generalized implementation of a variant of the well-known space vector modulation featuring lower losses is proposed in this work. The derived relations to select a particular switching sequence are based on the binary logic and symmetry of the possible states in such a three-level converter. The algorithm proposed in this work dynamically adjusts the switching sequences to accommodate capacitive as well as inductive behavior.
Keywords: Neutral-point-clamped (NPC) converters; bus clamping; space-vector modulation (SVM); pulse-width modulation (PWM); T-type NPC (TNPC); 620